EFL Prospective Teacher Educators’ Beliefs towards the Use of WhatsApp in English Learning and Teaching - Saiful, Jepri Ali (PAROLE: Journal of Linguistics and Education, 2018)
This study was aimed to investigate the beliefs of EFL prospective teacher educators towards the use of WhatsApp in English learning and teaching. This study used survey research design and the samples were 44 master students of Applied Linguistics Department who had academic degree of B.Ed in TEFL in one of state universities in Yogyakarta. This study found that EFL prospective teacher educators had favorable beliefs towards WhatsApp integration in English learning and teaching. They perceived true that the use of WhatsApp was sine qua non of increasing the learners’ English learning proficiency, motivation, autonomy, and language attitude and creating fun and enjoyable English learning atmosphere. Consequently, present English teachers should integrate WhatsApp smartphone application in English learning and teaching.